A comparative analysis of nutritional content changes in six Chinese cuisines prepared using industrial versus traditional hand-cooked modes - Wang, Xuan; Li, Jun; Wu, Xiaomeng; Fan, Sai; Wang, Zhu; Zhao, Yunfeng; Li, Jingguang; Chen, Dawei (Frontiers in Nutrition, 2025)
ObjectiveWith the rise of industrialized dishes, the quality differences between industrial and traditional hand-cooked modes are a major concern for the food industry and consumers. This study examined the nutrient content variations in Chinese cuisines between these two cooking modes, addressing a crucial research gap.MethodsTo account for moisture changes during cooking, water content in both raw ingredients and cooked dishes was adjusted, and nutrients were reported on a dry matter basis. The changes in nutrient content pre- and post-cooking were assessed by calculating the relative percentage of nutrient content in the cooked dishes in comparison to their levels in the raw ingredients. An independent t-test was employed to assess the significance of differences in the changes in nutrient content between industrial and traditional hand-cooked modes.ResultsMacronutrient levels remained relatively stable, with changes of less than 20% across most dishes for both cooking methods, with some exceptions noted. Fat-soluble vitamins A and D exhibited minor fluctuations, ranging from 2.6 to 39.4%, while vitamin E levels consistently increased. In contrast, water-soluble vitamins, specifically B1, B2, B3, and B6, experienced substantial decreases across all examined dishes. The fatty acid profiles were consistent with the fat content, and mineral content demonstrated a moderate increase under both cooking conditions. An inter-group t-test indicated no significant differences in nutrient content changes between the two cooking modes (p > 0.05), except for vitamin B6 retention, which was significantly lower in traditional hand-cooked modes compared to industrial modes (p < 0.05).ConclusionAmong the six Chinese cuisines analyzed, the changes in nutrient content did not significantly differ between industrial and traditional cooking methods, with the notable exception of vitamin B6 retention. These findings contribute to a deeper understanding of how different cooking techniques impact the nutritional value of food, providing valuable insights for dietary decision-making and food processing technologies.